2022
DOI: 10.7759/cureus.31109
|View full text |Cite
|
Sign up to set email alerts
|

All That We Need to Know About the Current and Past Outbreaks of Monkeypox: A Narrative Review

Abstract: Monkeypox is a rare, zoonotic viral illness that was initially endemic mainly to Africa. The virus later spread to non-African countries and, in 2022, it exploded on a global scale, with an unprecedented number of cases. The rapid, multi-country transmission, primarily in men who have sex with men (MSM), and evolving clinical manifestations and demographic traits of the current outbreak have raised serious concerns among the international health community. An in-depth inquiry into the past and present outbreak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…About 10% of patients require hospital treatment in the current global outbreak, mainly due to pain and bacterial superinfections [Fink et al, 2022; Gessain et al, 2022; Girometti et al, 2022; Patel et al, 2022; Thornhill et al, 2022]. This is in contrast to the disease severity observed in the endemic mpox areas in Africa, in which mpox outbreaks are associated with mortality rates of up to 12% [Mitjà et al, 2022; Qiu et al, 2022; Singh et al, 2022]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About 10% of patients require hospital treatment in the current global outbreak, mainly due to pain and bacterial superinfections [Fink et al, 2022; Gessain et al, 2022; Girometti et al, 2022; Patel et al, 2022; Thornhill et al, 2022]. This is in contrast to the disease severity observed in the endemic mpox areas in Africa, in which mpox outbreaks are associated with mortality rates of up to 12% [Mitjà et al, 2022; Qiu et al, 2022; Singh et al, 2022]…”
Section: Introductionmentioning
confidence: 99%
“…About 10% of patients require hospital treatment in the current global outbreak, mainly due to pain and bacterial superinfections [Fink et al, 2022;Gessain et al, 2022;Girometti et al, 2022;Patel et al, 2022;Thornhill et al, 2022]. This is in contrast to the disease severity observed in the endemic mpox areas in Africa, in which mpox outbreaks are associated with mortality rates of up to 12% [Mitjà et al, 2022;Qiu et al, 2022;Singh et al, 2022] Three antiviral drugs (tecovirimat (ST-246), brincidofovir (CMX001), cidofovir) are mainly considered for mpox treatment, although they have not undergone clinical testing for mpox treatment [DeLaurentis et al, 2022;Elsayed et al, 2022;Gessain et al, 2022;Huang et al, 2022;Mitjà et al, 2022;Rabaan et al, 2022]. Despite differences in the clinical presentation of the current mpox outbreak compared to previous ones [Gessain et al, 2022;Girometti et al, 2022;Hoffmann et al, 2022;Huang & Wang, 2022;Iñigo Martínez et al, 2022], recent findings indicated that these three drugs are still effective against the currently circulating mpox viruses in therapeutically achievable concentrations [Frenois-Veyrat et al, 2022;Warner et al, 2022;Bojkova et al, 2022].…”
Section: Introductionmentioning
confidence: 99%
“…MPX infection may present a range of signs and symptoms, including pruritus, fatigue, cough, arthralgia, diarrhea, vomiting, nausea, difficulty in breathing [4] , lymphadenopathy, chills, fever, muscle aches, headache, sore throat, and skin lesions [3] . The cutaneous rash is characterized by 10 to 150 [4] macules which evolve progressively into papules, vesicles, pustules, and crusts [5] .…”
mentioning
confidence: 99%
“…MPX infection may present a range of signs and symptoms, including pruritus, fatigue, cough, arthralgia, diarrhea, vomiting, nausea, difficulty in breathing [4] , lymphadenopathy, chills, fever, muscle aches, headache, sore throat, and skin lesions [3] . The cutaneous rash is characterized by 10 to 150 [4] macules which evolve progressively into papules, vesicles, pustules, and crusts [5] . These lesions may also be filled with a white fluid [4] and generally resolve within 3-4 weeks after symptom onset in most cases but other body sites may also be affected concomitantly, including mucosae, genitals, and conjunctivae [6] .…”
mentioning
confidence: 99%
“…The monkeypox virus remains untreatable, and patients with the disease rely primarily on supportive care to recover. To interrupt the spread of the disease, vaccines and aggressive preventive measures remain essential[6].…”
mentioning
confidence: 99%